From penitence to charity : pious women and the Catholic Reformation in Paris - Diefendorf, Barbara B., 1946- (OUP E-Books., 2004)
An analysis of female penitents and the revival of Catholic institutions and spirituality that produced a burst of religious construction during the French wars of religion. It argues that the spiritual imperatives of self-mortification and renunciation influenced not just those with religious careers but also the behaviour of devout lay women.